2022
DOI: 10.7717/peerj.14296
|View full text |Cite
|
Sign up to set email alerts
|

Validation of General Anxiety Disorder (GAD-7) questionnaire in Spanish nursing students

Abstract: Background Nursing students are at risk of anxiety during their university education. Objective To determine the psychometric characteristics of the General Anxiety Disorder (GAD-7) questionnaire in a population of university nursing students. Methods A cross-sectional study was carried out with 170 students at the University of Jaen (Spain) in 2022. An online questionnaire was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Validation studies have found the GAD-7 to have good construct validity and reliability. Validation studies among university students reported good internal consistencies, with Cronbach α values ≥ 0.85 in studies taking place in the United States of America, 0.903 among Spanish students and 0.892 among South African university students ( 32 , 40 , 41 ). The GAD-7 also displayed good convergent validity with the PHQ-9 and PHQ-ADS with coefficients ≥0.75 ( 30 ).…”
Section: Methodsmentioning
confidence: 96%
“…Validation studies have found the GAD-7 to have good construct validity and reliability. Validation studies among university students reported good internal consistencies, with Cronbach α values ≥ 0.85 in studies taking place in the United States of America, 0.903 among Spanish students and 0.892 among South African university students ( 32 , 40 , 41 ). The GAD-7 also displayed good convergent validity with the PHQ-9 and PHQ-ADS with coefficients ≥0.75 ( 30 ).…”
Section: Methodsmentioning
confidence: 96%
“…A study for screening the anxiety among pregnant Chinese women found the sensitivity of GAD-7 is 96.8%, and the specificity is 56.1% which proved the quality of GAD-7. Other studies also showed that GAD-7 is capable of detecting symptoms and generalized anxiety disorder, and it is a useful and simple tool for detecting anxiety-related problems ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sociodemographic variables, information on the studies, and characteristics of profile of the students were collected. To determine the level of anxiety, the generalized anxiety disorder scale (GAD‐7) was used, which has been validated in a population of nursing students in Spain 19 . The GAD‐7 questionnaire consists of 7 items, with four response options each, where each item scores from 0 to 3, with 21 being the maximum score and detecting the presence of anxiety from 5 points 20 .…”
Section: Methodsmentioning
confidence: 99%